PENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU SISWA SMPMQ KHAIRU UMMAH TENTANG PENGELOLAAN SAMPAH MELALUI PEMBELAJARAN BERBASIS PROYEK PEMBUATAN ECO ENZYME - Andi Zulfikar Syaiful; Hermawati Hermawati; Al-Gazali Al-Gazali (Pascasarjana Universitas Negeri Makassar, 2022)
on students' knowledge, attitudes and behavior in managing waste. This study uses a single case study design at Sekolah Menengah Pertama Menghafal Qur'an (SMPMQ) Khairu Ummah. The data were obtained through interviews, observations, and unofficial documents such as preparation steps for the learning process, learning modules, documentation, and activity reports which were used to explore the experience and skills of waste management acquired by students during project implementation. The significance of the increase in students' knowledge, attitudes, and behavior in managing waste is measured using a questionnaire. The findings show that students understand the negative impact of improper waste management. The observation results show good teacher preparation in the management of project-based learning. The results of the study also showed an increase in students' skills in 1) classifying waste materials that are easily decomposed and suitable for making eco enzymes, 2) determining the right conditions for fermentation to take place, 3) determining the quality of a fermented product through organoleptic observations. Through project-based learning activities for making eco enzymes, students can learn about the concept of reusing waste materials for the production of new materials such as eco enzymes. There was a very significant increase in the scores of students' knowledge, attitudes, and behavior in managing waste after learning based on the eco enzyme production project. Valuable experience through student project activities to manage waste into useful products is expected to help sustain their lifelong learning process so that it can contribute greatly to creating environmental balance.